Pengaruh Pupuk Kandang Bebek dan Pupuk NPK terhadap Pertumbuhan dan Hasil Cabai Rawit di Tanah Gambut - Sari, Natalia Wilhelmina Bella; Syafiuddin, Wasi’an; Rianto, Fadjar (JURNAL AGROPLASMA, 2024)
It is hoped that applying duck manure and NPK fertilizer to peat soil can increase its fertility. This is expected to encourage productivity in the growth and production of chille pepper if you want to develop it on peat soil. The research aims to: determine the combination of interactions between the use of duck manure and NPK fertilizer on the growth and yield of cayenne pepper on peat soil and determine the best combined dose of duck manure and NPK fertilizer on the growth and yield of cayenne pepper on peat soil. The research used a completely randomized factorial design (CRD) consisting of 2 factors, each repeated 3 times. The first factor is the dose of duck manure (B) consisting of: b₁= 10 tons/ha, b₂= 15 tons/ha and b₃= 20 tons/ha. The second factor is the dose of NPK (N) fertilizer consisting of: n₁= 200 kg/ha, n₂=150 kg/ha and n₃= 100 kg/ha. Observed variables: plant height, root volume, plant dry weight, number of fruit per plant, weight of fruit per plant, length per fruit and diameter per fruit. Research shows that: There was no interaction between duck manure and NPK fertilizer on the growth and yield of chille pepper on peat soil. Providing 15 tons/ha of duck manure equivalent to 529 g/polybag is an effective dose for height growth and dry weight of cayenne pepper plants on peat soil. Providing NPK fertilizer of 100 kg/ha equivalent to 3.52 g/polybag is the best dose to provide dry weight growth of chille pepper plants in peat soil. Keywords: chille pepper, duck manure, NPK fertilizer, peat soil